Durability life evaluation of marine infrastructures built by using carbonated recycled coarse aggregate concrete due to the chloride corrosive environment - Jiang, Han; Wu, Linjian; Guan, Li; Liu, Mingwei; Ju, Xueli; Xiang, Zhouyu; Jiang, Xiaohui; Li, Yingying; Long, Jia (Frontiers in Marine Science, 2024)
Due to the harsh marine environment of chloride ion invasion and corrosion, the issues of long-term chloride transport and durability life evaluation for marine infrastructures constructed/maintained by recycled aggregate concrete (RAC) after enhancement remain poorly understood. For our studies, an accelerated carbonation modification method for recycled coarse aggregate (RCA) was adopted to prepare carbonated recycled coarse aggregate (CRCA) samples, and the macroproperties, i.e., apparent density and water absorption, of CRCA were enhanced by approximately 1.40-3.97% and 16.3-21.8%, respectively, compared with those of RCA. An in-door experiment for chloride transport into concrete specimens subjected to a simulated marine environment of alternating drying-wetting cycles was conducted. The chloride profiles and transport characteristics of carbonated recycled coarse aggregate concrete (CRCAC), recycled coarse aggregate concrete (RCAC), and natural coarse aggregate concrete (NCAC) were analysed and compared. The results indicated that the chloride penetration depths and concentrations of CRCAC were approximately 52.6-96.2% of those of RCAC, which highlighted the better chloride resistance of CRCAC. A chloride transport model for marine concrete structures with various coarse aggregate types in a corrosive marine environment was established. Taking a certain harbour wharf as an example, the durability life of this case considering the application of the CRCAC was evaluated based on the chloride transport model, and the durability life of the CRCAC structure was improved by approximately 28.10% compared with that of the RCAC. The CRCAC developed in this paper has improved mechanical performance and durability than those of RCAC, and it has the potential to replace the NCAC and further support the construction and maintenance of marine infrastructures.